2014
DOI: 10.5194/acp-14-6669-2014
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric tar balls: aged primary droplets from biomass burning?

Abstract: Abstract. Atmospheric tar balls are particles of special morphology and composition that are fairly abundant in the plumes of biomass smoke. These particles form a specific subset of brown carbon (BrC) which has been shown to play a significant role in atmospheric shortwave absorption and, by extension, climate forcing. Here we suggest that tar balls are produced by the direct emission of liquid tar droplets followed by heat transformation upon biomass burning. For the first time in atmospheric chemistry we ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 23 publications
4
71
3
Order By: Relevance
“…Briefly, liquid tar was produced from dry distillation of 2 different wood types (Robinia pseudoacacia (black locust) and Picea abies (Norway spruce)) similar to that described in Tóth et al (2014). The obtained liquid distillate consisted of an aqueous phase and an oily 20 phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, liquid tar was produced from dry distillation of 2 different wood types (Robinia pseudoacacia (black locust) and Picea abies (Norway spruce)) similar to that described in Tóth et al (2014). The obtained liquid distillate consisted of an aqueous phase and an oily 20 phase.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Tóth et al (2014) have demonstrated that tar balls very similar to those observed in the atmosphere can be directly produced in the laboratory from liquid tar obtained by the dry 5 distillation of wood. This lab experiment postulates that during biomass combustion direct ejection of liquid tar droplets from the pores followed by atmospheric aging generates tar ball particles in biomass smoke plumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works (Tóth et al, 2014;Hoffer et al, 2016) an experimental setup has been developed for the generation of TB particles in the laboratory without the concurrent emission of other combustion products. The morphological and structural characteristics and the elemental composition of the TB particles generated by this experimental system were highly similar to those of atmospheric TBs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the chemical properties of TBs can only be studied by single-particle analytical techniques such as TEM-EDS or SEM-EDS Pósfai et al, 2003Pósfai et al, , 2004Hand et al, 2005;Niemi et al, 2006;Adachi and Buseck, 2011;Chakrabarty et al, 2016;Adachi et al, 2017;Cong et al, 2009Cong et al, , 2010China et al, 2013;Chakrabarty et al, 2006Chakrabarty et al, , 2010Semeniuk et al, 2007), TEM with electron energy-loss spectroscopy (TEM-EELS) (Hand et al, 2005, Adachi andBuseck, 2011), and near-edge X-ray absorption fine-structure spectroscopy (NEXAFS) using a synchrotron source (Tivanski et al, 2007). In our previous works (Tóth et al, 2014;Hoffer et al, 2016) an experimental setup had been developed for the generation of TB particles in the laboratory without the concurrent emission of other combustion products. The structural characteristics (homogeneity) and the elemental composition of the TB particles generated by this experimental system were highly similar to those of atmospheric TBs published by Pósfai et al (2004) and Adachi and Buseck et al (2011) as the Lab-TBs have homogenous internal structure without core and concentrically wrapped graphitic layers.…”
Section: Introductionmentioning
confidence: 99%